The Legal Power of Electronic Contracts and as Evidence In default during the Covid-19 Pandemic in Indonesia - Anggun Lestari Suryamizon; Kartika Dewi Irianto; Mahlil Adriaman (Indonesian Journal of Law and Policy Studies, 2022)
An agreement is a legal act that will create a legal relationship between one legal subject and another to fulfill an achievement. In Indonesia, in general, people carry out business activities accompanied by a written agreement or what is commonly referred to as a contract. At this time, Indonesia is being affected by the Covid-19 virus and has become a national disaster. With this national disaster, it has greatly affected the lives of the Indonesian people, especially in the business sector, in which the implementation transaction must be accompanied by a contract where each business transaction will certainly experience a decline and setback which will result in many parties involved in the contract unable to fulfill their achievements. Especially when the current conditions of many parties agree to their agreement by using electronic contracts to anticipate the possibility of the spread of the corona virus. This study aims to (1) find out how the implementation of electronic contracts during the pandemic, and (2) how the validity and strength of electronic contracts. This research is very interesting to study because electronic contracts are new in the world of contract law, and it examines more deeply how the proof will be and its legal strength when there is default in the implementation of the electronic contract. The method used is juridical normative. This study will provide an explanation of the legal strength of electronic contracts, and how the strength of proof is in case of default.